Patofisiologi Trigger Finger pada PenderitaCarpal Tunnel Syndrome dan Diabetes Melitus - Atina Rizki Putri; Nurhidayati; Made Raditya Arhya Putra; I Made Tobias Abdiman; Saskia Safarinaa Hazaa; Illiyani Sholihatin; Yusril Sani Riandika Putra; Gintis Dhimar Ginuluh; Safira Said Hayaza; Ekawaty Retnaningsih; Sabila Izzatina Azmy Mujahid (LPPM STIKES Mataram, 2024)
Introduction: Trigger finger or stenosis tenosynovitis is a nodule-like swelling of the flexor muscle tendon in the metacarpophalangeal region that can be triggered by repetitive motion or comorbid diseases such as diabetes mellitus and carpal tunnel syndrome. Objective: To review the knowledge of trigger finger, especially those caused by DM and CTS in relation to its etiology, pathophysiology, clinical manifestations, and management. Methods: The author conducts a literature search for relevant articles about trigger finger, expeciali its related DM and CTS by determining literature sources in the form of official books, national and international journals published until January 2019. This research literature search was conducted through Google Scholar, Medline (PubMed), NCBI, sciencedirect and trusted journal publishers. Results: It was found that the annual incidence of trigger finger reached 28 cases per 100,000 and the prevalence reached 2.6% in the general population. The sufferers are in the age range of 50-84 years and predominantly occur on the right hand (60% of cases). Several studies describe the percentage of success of several trigger finger management methods, for example, the corticosteroid injection method has a success rate of 67%-90%, subcutaneous surgery with a success rate of 73.8%-100%. Conclusion: Trigger finger is a condition of swelling of the metacarpophalangeal flexor tendon that can be caused by several comorbid diseases, such as diabetes mellitus and carpal tunnel syndrome. Until now, several treatments that can be given are pharmacological therapy or non-pharmacological therapy.